2019
DOI: 10.1111/ajt.15100
|View full text |Cite
|
Sign up to set email alerts
|

The effect on early renal function of various dynamic preservation strategies in a preclinical pig ischemia–reperfusion autotransplant model

Abstract: The aims of this study were to determine the most optimal timing to start machine perfusion during kidney preservation to improve early graft function and to evaluate the impact of temperature and oxygen supply during machine perfusion in a porcine ischemia-reperfusion autotransplant model. The left kidney of an approximately 40-kg female Belgian Landrace pig was exposed to 30 minutes of warm ischemia via vascular clamping and randomized to 1 of 6 study groups: (1) 22-hour static cold storage (SCS) (n = 6), (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 40 publications
6
70
0
Order By: Relevance
“…Moreover, recipients in HOPE-K with DGF had undergone perfusion treatment for less than two hours, as compared to non-DGF patients which actually underwent perfusion treatment for more than 2 hours. Therefore, based on our experience, we suggest that kidney perfusion should last at least two hours; this treatment time could be possibly longer, as suggested by a pre-clinical study 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, recipients in HOPE-K with DGF had undergone perfusion treatment for less than two hours, as compared to non-DGF patients which actually underwent perfusion treatment for more than 2 hours. Therefore, based on our experience, we suggest that kidney perfusion should last at least two hours; this treatment time could be possibly longer, as suggested by a pre-clinical study 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Anesthetic and surgical protocols were followed as described previously. 6,7 The left kidney was removed after 30 minutes of warm ischemia induced by vascular clamping of the renal vessels and subsequently flushed with 200 mL of Kidney Perfusion Solution (KPS-1, Organ Recovery Systems, Diegem, Belgium). The kidney was randomized to one of the following preservation strategies: (1) 2-hour oxygenated HMP (90% oxygen) (HMPO 2 ) + 20-hour HMP with no additional oxygen (n = 6) or (2) 20-hour HMP followed by 2-hour HMPO 2 (n = 5).…”
Section: Anesthetic and Surgical Protocolmentioning
confidence: 99%
“…We recognize that there are a number of limitations inherent to this porcine autotransplant. 6 The use of historical control groups might have introduced a relevant bias due to slightly shorter anastomosis time in the experimental study groups compared with one of the historical groups but was recommended by the ethics committee to reduce animal numbers and suffering. However, because total preservation time was comparable between all study groups we do not expect to have an important influence on the outcome measures.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…The same group showed that kidney assessment during warm perfusion might lead to transplantation of initially discarded DCD kidneys [49]. Extending normothermic perfusion to longer periods (2 to 8 hours) has been explored in pig studies [50][51][52][53][54]. Kidneys not suitable for transplantation have been normothermically perfused for 24 hours, making use of urine recirculation, though not transplanted [55].…”
Section: Normothermic Kidney Perfusionmentioning
confidence: 99%